The March to Prussia: The Informative Value of a Peripheral Phenomenon - Werner Paravicini (Lietuvos Istorijos Studijos)
This article not only introduces new sources that underline the importance of the march to Prussia (Preußenreisen) for the nobility of Western Europe at the time, but also highlights the challenges they faced along the way, including encounters with marauders, adverse natural conditions and captivity. These campaigns provide a detailed insight into the life of European nobility: how nobles inspired by literary ideals embarked on long journeys, visited various courts and feasted with other knights, and finally how European chivalry conceived itself on these campaigns. The story tells how from the westernmost corner of Europe they travelled to the East and, on their return, tried to make sense of their journeys (despite the enormous expense) through places of memory. In addition, this study explores how the Teutonic Order faced the new challenge of seeking new legitimacy after the baptism of Lithuania and Samogitia.